Proton-conducting ceramic electrochemical cell with composite cathode
Patent Information
- Application Number
- JP2026514528
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-11-13
- Filing Date
- 2024-09-05
- Publication Date
- 2026-10-14
Smart Images

Figure 2026533997000001_ABST
Abstract
Description
[Technical Field]
[0001] Related applications This application claims priority to U.S. Provisional Patent Application No. 63 / 598,327, entitled “PROTONIC CERAMIC ELECTROCHEMICAL CELLS HAVING COMPOSITE POSITIVE ELECTRODE,” filed on 13 November 2023, and to U.S. Provisional Patent Application No. 63 / 580,917, entitled “PROTONIC CERAMIC ELECTROCHEMICAL CELLS HAVING COMPOSITE POSITIVE ELECTRODE,” filed on 6 September 2023, the full disclosures of which are incorporated herein by reference.
[0002] This disclosure generally relates to cathodes that can be used in proton-conducting ceramic electrochemical cells ("PCECs"). More specifically, this disclosure generally relates to cathodes comprising solid composite materials comprising a double perovskite phase and a single perovskite phase. [Background technology]
[0003] For efficient power generation and green hydrogen production, ceramic electrochemical cells based on both oxygen ion conductors and proton-conducting oxides have been demonstrated. Compared to low-temperature polymer electrolyte membrane electrochemical cells, ceramic electrochemical cells offer significant advantages, including fuel flexibility in fuel cell mode and higher energy efficiency in steam electrolysis mode. However, the scale-up and commercialization of ceramic electrochemical cells lags behind that of polymer electrolyte membrane electrochemical cells, mainly due to the high operating temperatures (above 500°C) of ceramic electrochemical cells. Therefore, fabricating low-temperature ceramic electrochemical cells is one of the major challenges and opportunities in this research field.
[0004] The operating temperature of solid oxide electrochemical cells based on oxygen ion conductors ("O-SOEC") has been successfully reduced to approximately 500°C. However, due to the relatively high activation energy of oxygen ion conduction, it is difficult to reduce the operating temperature of O-SOEC below 450°C. Because proton conduction has a lower activation energy than oxygen ion conduction, proton-conducting ceramic electrochemical cells ("PCEC") have been repeatedly studied and proposed to operate below 450°C.
[0005] Only a handful of studies have reported that PCECs can operate below 450°C. Haile et al. found that depositing a dense interfacial layer between the electrolyte and the cathode reduced the ohmic resistance in H2-air at 450°C, resulting in a peak power density (PPD) of 0.36 Wcm². -2 They demonstrated that it increases. Ding et al. used a complex template method to reduce electrode polarization resistance in highly porous PrBa 0.5 Sr 0.5 Co 1.5 Fe 0.5 O 6-δ A cathode ("PBSCF-1") was fabricated, which improved mass transport dynamics and produced 0.41 Wcm³ of H2-O2 at 400°C. -2 This resulted in a PPD of 0.65 Wcm² for H2-O2 at 450°C. In a recent study by the same team, using an acid-etched electrolyte and a cathode fabricated via this template method, a PPD of 0.65 Wcm² for H2-O2 was obtained. -2 Further increases have been reported. However, most of these methods are complex or not scalable. Therefore, a simpler and more scalable method is desired for fabricating PCECs with low-resistance electrolytes and active cathodes to achieve good PCEC performance below 450°C.
[0006] A discrepancy has been observed between the inherent electrolyte conductivity and the ohmic conductivity of PCECs, which suggests that PCECs promote additional ohmic resistance, mainly including high electrolyte-grain boundary resistance and positive electrode-electrolyte contact resistance. Therefore, PCECs should be better fabricated to optimize their microstructures, with the aim of minimizing grain boundary resistance while strengthening the bond between the electrode and the electrolyte, especially the weakly bonded positive electrode-electrolyte interface formed in another high-temperature process. Furthermore, it is widely recognized that the oxygen reduction reaction ("ORR") and oxygen evolution reaction ("OER") occurring at the positive electrode tend to become slower as the operating temperature decreases. These results suggest that both the electrolyte and the positive electrode should be optimized to enhance PCEC performance below 450°C. SUMMARY OF THE INVENTION
[0007] One or more embodiments generally relate to a positive electrode that can be used for proton-conducting ceramic electrochemical cells (PCECs) comprising a solid composite material including a double perovskite phase and a single perovskite phase. The double perovskite phase includes PrBaSrCoFeO (PBSCF), and the single perovskite phase includes BaSrCoO (BSC).
[0008] One or more embodiments generally relate to a positive electrode comprising a solid composite material. The solid composite material has the formula Pr a Ba b Sr c Co d Fe e O 6-δ1 and a single perovskite phase having the formula Ba x Sr y Co z O 3-δ2 , where in the formula, a is from 1 to 1.75, b is from 0.05 to 0.5, c is from 0.3 to 0.7, d is from 1.25 to 1.75, e is from 0.4 to 0.9, δ1 is greater than 0 but less than 1. x is between 0.4 and 0.75. y is between 0.25 and 0.5. z is between 0.75 and 1.25. δ² is greater than 0 but less than 0.5.
[0009] One or more embodiments generally relate to a proton-conducting ceramic electrochemical cell (PCEC) comprising a positive electrode formed from a solid composite material according to any embodiment described herein. The PCEC further comprises a negative electrode comprising any conventional material for such an electrode, including but not limited to BCZYYb7111 and NiO. The PCEC also comprises an electrolyte disposed between the oxygen electrode and the fuel electrode. The electrolyte may be any conventional electrolyte material, including but not limited to BCZYYb4411. In certain embodiments, the positive and negative electrodes have a thickness of at least 10 μm, 10–100 μm, 15–75 μm, or 20–50 μm. In certain embodiments, the electrolyte material has a thickness of at least 1 μm, 1–30 μm, 2–20 μm, or 5–15 μm.
[0010] One or more embodiments relate to a method for producing hydrogen in general. Generally, the method provides a proton-conducting ceramic electrochemical cell as described herein, and includes reacting water at the negative electrode to produce oxygen and protons, allowing the protons to pass through a proton-conducting electrolyte to reach the positive electrode, and supplying an electric current to the negative electrode to reduce at least a portion of the protons to form hydrogen.
[0011] One or more embodiments relate to a method for generating electricity in general. Generally, the method provides a proton-conducting ceramic electrochemical cell as described herein, and includes supplying hydrogen to the electrochemical cell, oxidizing the hydrogen at a first electrode to form protons and electrons, allowing the protons to pass through a proton-conducting electrolyte to reach a second electrode, inducing an electric current in the electrons generated at the second electrode, passing the current through an electrical load connected to the second electrode and the first electrode, and reacting the protons with oxygen at the second electrode to produce water.
[0012] Embodiments of the present invention will be described herein with reference to the following drawings. [Brief explanation of the drawing]
[0013] [Figure 1] This figure shows an exemplary proton-conducting ceramic electrochemical cell, including electrodes formed from the solid composite materials described herein.
[0014] [Figure 2] (a) is a schematic diagram of a PCEC electrolyte fabricated using an ultrasonic spray coater, and (b) is a schematic diagram of a PCEC electrolyte fabricated using a conventional airbrush. [Modes for carrying out the invention]
[0015] Solid composite materials have been developed that can be used for a variety of applications, including forming electrodes in electrochemical cells. The solid composite materials described herein may include a double perovskite phase and a single perovskite phase. Due to their unique chemical composition, electrodes and electrochemical cells exhibiting superior performance may be manufactured using the solid composite materials disclosed herein. For example, it has been discovered that a positive electrode can be formed from a solid composite material that can be used in a proton-conducting ceramic electrochemical cell ("PCEC"), and that it exhibits superior performance. More specifically, it has been discovered that a high-performance, low-temperature (below 450°C) PCEC ("LT-PCEC") can be manufactured using the solid composite materials described herein.
[0016] A proton-conducting ceramic electrochemical cell can be provided, comprising a positive electrode comprising a solid composite material according to any embodiment described herein, as will be described in more detail below. The PCEC further comprises a negative electrode comprising any conventional material for such an electrode, comprising but not limited to BCZYYb7111 and NiO. Furthermore, the PCEC comprises an electrolyte disposed between the positive and negative electrodes. The electrolyte may be any conventional electrolyte material, comprising but not limited to BCZYYb4411. In certain embodiments, the positive and negative electrodes have a thickness of at least 10 μm, 10–100 μm, 15–75 μm, or 20–50 μm. Additionally or alternatively, the electrolyte material has a thickness of at least 1 μm, 1–30 μm, 2–20 μm, or 5–15 μm.
[0017] solid composite material According to various embodiments, solid composite materials comprising a double perovskite phase and a single perovskite phase may be produced. The double perovskite phase comprises PrBaSrCoFeO ("PBSCF"), and the single perovskite phase comprises BaSrCoO ("BSC").
[0018] As used herein, the terms “perovskite” and “single perovskite phase” mean any material having a crystalline structure having the formula ABX3, where “A” and “B” represent cations and “X” represent an anion. Furthermore, as used herein, “double perovskite” means a composite perovskite material having a crystalline structure AA'BB'X6, where “A” and “A'” represent two or more cations, e.g., alkaline earth metals and / or rare earth metals, “B” and “B'” represent two or more cations, e.g., cations containing transition metals, and “X” represent at least one anion. Generally, in various embodiments, a two-phase perovskite may have twice the number of unit cells of a single perovskite phase, with two cations ordered at the “B” sites.
[0019] Generally, in one or more embodiments, solid composite materials such as a double perovskite phase and a single perovskite phase may be synthesized using a wet chemical process, in which two or more cations and one or more anions are dissolved in water in stoichiometric amounts. An example of a precursor reagent for the cations and / or anions is, for example, Pr6O 11 It may also contain Ba(NO3)2, Sr(NO3)2, Co(NO3)·6H2O, Fe(NO3)3·9H2O and / or Fe(NO3)3·6H2O.
[0020] During the wet chemical process, in one or more embodiments, Ba(NO3)2, Sr(NO3)2, Co(NO3)3·6H2O and Fe(NO3)3·6H2O (or Fe(NO3)3·9H2O) may be dissolved at least partially in stoichiometric amounts in deionized water to form an initial reaction solution. Furthermore, a specific amount of Pr6O 11 It may be dissolved in dilute nitric acid and then added to the reaction solution. For example, the calculated amount of Pr6O 11The praseodymium nitrate solution may be obtained by dissolving it in a dilute nitric acid solution of about 20 wt percent at about 100°C. The praseodymium nitrate solution may be added to the reaction solution while stirring for 10 to 60 minutes, 15 to 45 minutes, or 30 minutes at a temperature in the range of about 15 to about 100°C, about 20 to about 80°C, or about 20 to about 50°C.
[0021] In one or more embodiments, the reaction solution is (a) 0.05-0.5 moles, 0.1-0.4 moles, or 0.15-0.25 moles of Pr6O 11 , (b) 0.05-1.0 moles, 0.1-0.8 moles, or 0.3-0.6 moles of Ba(NO3)2, (c) 0.05-1.0, 0.1-0.8, or 0.3-0.6 moles of Sr(NO3)2, (d) 0.1–2.0 moles, 0.5–1.9 moles, or 1.0–1.7 moles of Co(NO3)3 and / or (e) Contains 0.05 to 1.0 moles, 0.1 to 0.8 moles, or 0.3 to 0.6 moles of Fe(NO3)3.
[0022] In one particular embodiment, the reaction solution contains about 0.17 moles of Pr6O 11 It contains approximately 0.5 moles of Ba(NO3)2, approximately 0.5 moles of Sr(NO3)2, approximately 1.5 moles of Co(NO3)3, and approximately 0.5 moles of Fe(NO3)3.
[0023] After forming the initial reaction solution, one or more complexing agents and chelating agents, such as citric acid ("CA") and / or ethylenediaminetetraacetic acid ("EDTA"), may be added to the reaction solution. The complexing agents and chelating agents may be added to the reaction solution with continuous stirring for 10 to 90 minutes, 15 to 75 minutes, or 60 minutes at a temperature in the range of about 15 to about 100°C, about 20 to about 80°C, about 20 to about 50°C, or about 23°C, in order to obtain complete complexation.
[0024] In one or more embodiments, after adding the complexing agent and chelating agent, the molar ratio of CA:total cations in the resulting reaction solution may be at least 1:1, 1.5:1, or 2:1, and / or less than 4:1, 3.5:1, or 3:1. Additionally or alternatively, after adding the complexing agent and chelating agent, the molar ratio of EDTA:total cations in the resulting reaction solution may be at least 1:1, 1.5:1, or 2:1, and / or less than 4:1, 3.5:1, or 3:1. In certain embodiments, after adding the complexing agent and chelating agent, the molar ratio of CA:EDTA:total cations in the resulting reaction solution may be about 2:2:1.
[0025] Next, after adding the complexing agent and chelating agent, the pH of the resulting reaction solution may be adjusted to approximately 9 by adding a pH adjusting agent (for example, an aqueous solution of NH4OH).
[0026] After adjusting the pH of the reaction solution, the reaction solution may be heated to form a gel. Generally, in one or more embodiments, the reaction solution may be heated to a temperature in the range of about 200 to about 400°C, about 225 to about 350°C, or about 250 to about 300°C. The reaction solution may be heated using conventional apparatus known in the art, for example, by a hot plate or oven, until a gel is formed.
[0027] Once the gel is formed, at least a portion of the resulting gel may be immediately placed in a drying oven or other drying device for further drying. In one or more embodiments, the drying process may be carried out at a temperature in the range of about 50 to about 250°C, about 75 to about 225°C, about 100 to about 200°C, or about 175°C for a period of about 3 to about 36 hours, about 6 to about 30 hours, or about 24 hours.
[0028] After drying, in various embodiments, the resulting powder may then be calcined under air at a temperature in the range of about 400 to about 700°C, about 500 to about 675°C, or about 600 to about 650°C for 1 to 24 hours, 2 to 18 hours, 3 to 8 hours, or about 5 hours.
[0029] Subsequently, in various embodiments, at least a portion of the calcined powder may be subjected to grinding, such as ball milling, in alcohol (e.g., ethanol) for 1 to 48 hours, 6 to 36 hours, or about 24 hours. At least a portion of the ground powder may then be dried in a dryer (e.g., a drying oven) at temperatures ranging from about 50 to about 250°C, about 75 to about 225°C, about 100 to about 200°C, about 100°C, or about 175°C for a period of about 3 to about 36 hours, about 6 to about 30 hours, or about 24 hours.
[0030] Finally, in various embodiments, the dry-sintered powder may be sintered at temperatures ranging from about 500 to about 900°C, about 600 to about 800°C, or about 750 to about 775°C until the dry-sintered powder crystallizes into a solid composite material comprising a double perovskite phase and a single perovskite phase. In various embodiments, the resulting solid composite material may be in the form of a powder.
[0031] In one or more embodiments, the phase structures within the double perovskite phase and the single perovskite phase are such that each perovskite has a structure that is distinctly identifiable within the whole material, and each phase has its own identifiable crystalline structure.
[0032] In one or more embodiments, the solid composite material is given by formula Pr a Ba b Sr c Co d Fe e O 6-δ1 A double perovskite phase having the formula Ba x Sr y Co z O 3-δ2 It comprises a single perovskite phase having, in the formula, a is 1-1.75, 1.1-1.6, 1.2-1.5, or 1.3-1.5. b is 0.05-0.5, 0.05-0.4, 0.05-0.3, or 0.1-0.2. c is 0.3-0.7, 0.35-0.65, or 0.4-0.6. d is 1.25-1.75, 1.3-1.7, or 1.35-1.65. e is between 0.4 and 0.9, 0.5 and 0.85, or 0.6 and 0.8. δ1 is greater than 0 but less than 1. x is between 0.4 and 0.75, 0.45 and 0.7, or 0.5 and 0.7. y is between 0.25 and 0.5, 0.3 and 0.45, or 0.3 and 0.4. z is between 0.75 and 1.25, 0.8 and 1.2, or 0.9 and 1.1. δ² is greater than 0 but less than 0.5.
[0033] In one or more embodiments, the solid composite material is given by formula Pr a Ba b Sr c Co d Fe e O 6-δ1 A double perovskite phase having the formula Ba x Sr y Co z O 3-δ2 It comprises a single perovskite phase having, in the formula, a is between 1 and 1.75. b is between 0.05 and 0.5. c is between 0.3 and 0.7. d is between 1.25 and 1.75. e is between 0.4 and 0.9. δ1 is greater than 0 but less than 1. x is between 0.4 and 0.75. y is between 0.25 and 0.5. z is between 0.75 and 1.25. δ² is greater than 0 but less than 0.5.
[0034] In one or more embodiments, the solid composite material has a molar ratio of barium to strontium in the double perovskite phase of 0.1:1 to 1:1, 0.2:1 to 0.8:1 or 0.2:1 to 0.5:1, a molar ratio of praseodymium to barium in the double perovskite phase of 1.5:1 to 15:1, 2:1 to 14:1, 3:1 to 13:1 or 4:1 to 12:1, a molar ratio of praseodymium to strontium in the double perovskite phase of 1.5:1 to 3.5:1, 2:1 to 3.5:1 or 2.5:1 to 3.5:1, and a molar ratio of praseodymium to cobalt in the double perovskite phase of 0.5:1 to 1.5:1. The molar ratios of praseodymium to iron in the double perovskite phase are 0.7:1 to 1.4:1 or 0.8 to 1.3:1, 1.5:1 to 2.5:1, 1.6:1 to 2.4:1 or 1.7:1 to 2.3:1, barium to strontium in the single perovskite phase is 1.5:1 to 2.0:1 or 1.6:1 to 1.95:1, barium to cobalt in the single perovskite phase is 0.5:1 to 0.75:1 or 0.6:1 to 0.7:1, and / or strontium to cobalt in the single perovskite phase is 0.25:1 to 0.5:1 or 0.3:1 to 0.45:1.
[0035] In one or more embodiments, the solid composite material has a molar ratio of barium to strontium in the double perovskite phase of 0.1:1 to 1:1, a molar ratio of praseodymium to barium in the double perovskite phase of 1.5:1 to 15:1, a molar ratio of praseodymium to strontium in the double perovskite phase of 1.5:1 to 3.5:1, and a molar ratio of praseodymium to cobalt in the double perovskite phase of 0.5: The molar ratio of praseodymium to iron in a double perovskite phase is 1.5:1 to 2.5:1, the molar ratio of barium to strontium in a single perovskite phase is 1.5:1 to 2.0:1, the molar ratio of barium to cobalt in a single perovskite phase is 0.5:1 to 0.75:1, and / or the molar ratio of strontium to cobalt in a single perovskite phase is 0.25:1 to 0.5:1.
[0036] In exemplary embodiments, the double perovskite phase is Pr 1.44 Ba0.11 Sr 0.45 Co 1.32 Fe 0.68 O 6-δ The formula is such that the single perovskite phase is Ba 0.62 Sr 0.38 OO 3-δ It has the formula -
[0037] In another exemplary embodiment, the double perovskite phase is Pr 1.39 Ba 0.14 Sr 0.53 Co 1.48 Fe 0.76 O 6-δ - has the formula, and the single perovskite phase is Ba 0.66 Sr 0.34 OO 3-δ It has the formula:
[0038] In one or more embodiments, the double perovskite phase has a tetragonal (P4 / mmm) crystal structure, and / or the single perovskite phase has a hexagonal P63 / mmc crystal structure, as confirmed by transmission electron microscopy ("TEM") and X-ray diffraction ("XRD").
[0039] The crystalline structure of the as-synthesized powder was measured using XRD (Rigaku MiniFlex diffractometer with a CuKα radiation source operating at 30kV and 15mA). The scanning speed was 1° / min. The morphology, microstructure, and chemical composition of the solid composite material were investigated using a transmission electron microscope ("TEM", FEI Tecnai Osiris 200Kv S / TEM system and Talos F200X S / TEM system, operating at 200kV, equipped with a FEG (field emission gun) cathode and four in-column Super-X energy-dispersive X-ray spectroscopy (EDS) detectors with a total collection angle of 0.9sr). The microstructure of PCEC was investigated using a scanning electron microscope (Hitachi / S-3400N).
[0040] In one or more embodiments, the solid composite material comprises at least 25, 30, 35, 40, 45, 50, 55, 60, 65, or 70 wt% of the double perovskite phase. Additionally or alternatively, the solid composite material may comprise less than 99, 95, 90, 85, 80, or 75 wt% of the double perovskite phase. In certain embodiments, the solid composite material comprises about 70 wt% of the double perovskite phase. These wt%s and the wt%s disclosed below may be confirmed by XRD.
[0041] In one or more embodiments, the solid composite material comprises at least 1, 5, 10, 15, 20, or 25 wt% of a single perovskite phase. Additionally or alternatively, the solid composite material may comprise less than 60, 50, 45, 40, or 35 wt% of a single perovskite phase. In certain embodiments, the solid composite material comprises about 30 wt% of a single perovskite phase.
[0042] In one or more embodiments, the solid composite material may have an average particle size of at least 1, 5, 10, 15 or 20 nm, and / or less than 100, 90, 85, 80, 75, 70, 65, 60, 55, 50, 45 or 40 nm, as confirmed by TEM.
[0043] Proton-conducting ceramic electrochemical cell The solid composite materials described herein may be used in a variety of applications. In one or more embodiments, the solid composite materials may be used to manufacture electrodes for generating electricity in electrochemical cells such as fuel cells. Generally, fuel cells are electrochemical cells that convert chemical energy into electricity by reacting hydrogen fuel with oxygen or other oxidizing agents. An exemplary fuel cell that can be manufactured from electrodes containing the solid composite materials described herein is a proton-conducting ceramic electrochemical cell ("PCEC").
[0044] As shown in Figure 1, and as will be described in more detail below, the proton-conducting ceramic electrochemical cell 10, which includes electrodes formed from the solid composite material described herein, includes a negative electrode 12, an electrolyte 14 in contact with the negative electrode 12, and a positive electrode 16 in contact with the electrolyte 14.
[0045] Various methods for overcoming the aforementioned challenges and fabricating high-performance low-temperature (below 450°C) PCECs ("LT-PCECs") are described herein.
[0046] This disclosure also relates to a method for forming a proton-conducting ceramic electrochemical cell ("PCEC") using the solid composite materials described herein. In one or more embodiments, the method includes (a) forming a single or double negative electrode 12 on a temporary substrate; (b) forming an electrolyte 14 on the negative electrode 12 to form a laminate; (c) optionally sintering the laminate to form part of an electrochemical cell 10; (d) forming a positive electrode 16 on the electrolyte 14 to form a second laminate comprising the negative electrode 12, the electrolyte 14 and the positive electrode 16; and (f) optionally sintering the second laminate to form an electrochemical cell 10.
[0047] In one or more embodiments, the electrochemical cell 10 includes a negative electrode 12. Although referred to as the "negative electrode," it will be understood that, depending on the operating mode used, the negative electrode 12 can function as either an anode or a cathode in the cell 10. In particular, when the cell 10 operates in hydrogen production mode, the negative electrode 12 (functioning as a cathode) reduces protons to hydrogen, and when the cell operates in electrogeneration mode, the first electrode (functioning as an anode) forms protons from hydrogen.
[0048] In one or more embodiments, the negative electrode 12 includes any conventional commercially available electrode material currently on the market. In a particular embodiment, the negative electrode 12 is BaCe 0.7 Zr 0.1 Y 0.1 Yb 0.1 O 3-δThe negative electrode 12 contains ("BCZYYb7111") and may be formed from BCZYYb7111. In certain embodiments, the negative electrode 12 contains at least 50, 75, 90, or 99% by weight of BCZYYb7111.
[0049] In one or more embodiments, the negative electrode powder is BaCe 0.7 Zr 0.1 Y 0.1 Yb 0.1 O 3-δ BCZYYb7111 may be composed of ("BCZYYb7111"), NiO, and cornstarch in a weight ratio of 2:3:1. It is widely recognized that an additional Ba reservoir can promote the densification of the electrolyte and mitigate elemental segregation, thereby improving proton conductivity. Therefore, an anode substrate with minimal non-stoichiometric Ba (i.e., low Ba deficiency) can promote electrolyte densification and proton conductivity. In various embodiments, BCZYYb7111 may be synthesized by rapid heating solid-phase sintering ("SSS") method. In such embodiments, stoichiometric amounts of BaCO3, CeO2, ZrO2, Y2O3, Yb2O3, and about 1 wt% NiO (the amount of NiO may be based on the total weight of crystallized BCZYYb7111) may first be ball-milled for about 48 hours. After drying at 120°C for 24 hours, the homogeneous mixture may be calcined in air at a rapid heating rate of 10°C / min at 1,350°C for 5 hours to crystallize BCZYYb7111, thereby maintaining the stoichiometry of Ba by reducing the vaporization of Ba during the anode powder crystallization process. The resulting chuck powder may then be pulverized into a fine powder, followed by ball milling and drying overnight at 120°C. The as-synthesized BCZYYb7111 fine powder may then be ball milled with NiO and corn starch for 48 hours. After drying at 120°C, a low-Ba deficient anode powder may be synthesized. During the subsequent co-sintering process, the low-Ba deficient anode substrate may function as a Ba reservoir to aid in electrolyte densification and maintain chemical homogeneity.
[0050] In one or more embodiments, the negative electrode functional layer powder contains at least 20, 30, or 40 weight percent and / or less than 80, 70, 60, or 50 weight percent of BaCe. 0.7 Zr 0.1 Y 0.1 Yb 0.1 O 3-δ It may consist of (BCZYYb7111) and at least 20, 30, 40, 50 or 60 weight percent and / or less than 95, 80, 70 or 65 weight percent of NiO. Addition of corn starch to the powder is optional.
[0051] In one or more embodiments, the negative electrode powder may be mixed with various additives (e.g., menhedene fish oil, b-98 polyvinyl butyral, polyethylene glycol 400, cyclohexanone, di-n-butyl phthalate and / or xylene) and alcohol (e.g., ethanol), and then ball-milled for a certain period of time (e.g., 24 hours) to obtain a negative electrode slurry.
[0052] In one or more embodiments, the negative electrode slurry may be coated onto a desired substrate (e.g., Mylar) by tape casting to form a negative electrode functional layer. After drying for a specified period (e.g., 5 hours in air), the negative electrode slurry may be cast onto the negative electrode functional layer. The two resulting layers may be dried (e.g., 48 hours in air) and then pre-sintered at about 800°C for about 30 minutes to thermally degrade all organic materials.
[0053] Once formed, the thickness of the negative electrode 12 may be in the range of approximately 10 μm to approximately 70 μm, approximately 20 μm to approximately 60 μm, approximately 30 μm to approximately 50 μm, or approximately 40 μm.
[0054] In one or more embodiments, the electrochemical cell 10 includes a proton-conducting electrolyte layer 14.
[0055] In one or more embodiments, the proton-conducting electrolyte layer 14 may be formed from any known or conventional electrolyte material currently available. In certain embodiments, the proton-conducting electrolyte layer 14 is BaCe 0.4 Zr 0.4 Y 0.1 Yb 0.1 O 3-δ It may be formed from ("BCZYYb4411").
[0056] In one or more embodiments, the electrolyte powder used to form the electrolyte layer 14 may be prepared by a wet chemical method to obtain nano-sized electrolyte powder. BaCe 0.4 Zr 0.4 Y 0.1 Yb 0.1 O 3-δ (BCZYYb4411) may be synthesized by a wet chemical process using a solution of Y2O3, Yb2O3, Ba(NO3)2, Ce(NO3)3·6H2O, and zirconyl nitrate (35% by weight in dilute nitric acid) as a precursor. Calculated amounts of Y2O3 and Yb2O3 may first be dissolved in a 20% by weight diluted nitric acid solution at 100°C to obtain a solution of yttrium nitrate and ytterbium nitrate. Subsequently, stoichiometric amounts of Ba(NO3)2, Ce(NO3)3·6H2O, and zirconyl nitrate may be added to the yttrium nitrate and ytterbium nitrate solution, followed by stirring for 30 minutes. Then, citric acid (CA) and ethylenediaminetetraacetic acid (EDTA), which are complexing and chelating agents, may be added to the above solution in a molar ratio of CA:EDTA:total cations of 2:2:1, and this may be stirred continuously at room temperature for 1 hour for complete complexation. Next, the pH may be adjusted to approximately 9 by adding an aqueous NH4OH solution. Then, the resulting solution may be heated at 250°C until a gel is formed. The gel is then dried in a drying oven at 175°C for 24 hours, and the powder is calcined at 1,250°C for 5 hours to obtain BCZYYb4411 electrolyte powder.
[0057] In various embodiments, the BCZYYb4411 electrolyte powder may be mixed with 1% by weight of NiO (the NiO acts as a sintering aid, and its amount is based on the mass of BCZYYb4411) and a binder (e.g., fish oil, b-98 polyvinyl butyral, di-n-butyl phthalate, and ethanol). The electrolyte powder may be mixed with specific amounts of fish oil, b-98 polyvinyl butyral, di-n-butyl phthalate, and ethanol to prepare a well-dispersed ink. To further improve dispersibility, the ink may be ball-milled for 4 days. The particle size distribution of the electrolyte powder in the ink may be evaluated using a Malvern Zetasizer Nano S. To ensure the reliability of these results, measurements may be performed three times. The obtained data may be analyzed using Mie theory. In certain embodiments, about 10% by volume of the powder exhibits a particle size of about 150 nm, while the majority of the powder exhibits a particle size of about 500 nm. In various embodiments, the average particle size may be 360–375 nm. Electrolyte powders with small particle sizes may be essential for obtaining an ultrathin and uniform electrolyte layer.
[0058] In one or more embodiments, an ultrasonic coating system may be used to fabricate an ultrathin (quasi-two-dimensional), chemically homogeneous, and robust proton-conducting electrolyte layer 14. In such embodiments, at least a portion of the electrolyte ink may be filled into an ultrasonic syringe. The flow rate of the electrolyte ink supplied to the ultrasonic nozzle may be controlled using a syringe pump. An ultrasonic nozzle mounted on an xyz robotic arm may be used to coat the ultrathin electrolyte layer. The coating time, spray spot size, coating rate, ultrasonic output, and substrate temperature may be optimized to achieve the desired electrolyte thickness and density. In certain embodiments, the resulting electrolyte layer 14 coated on the negative electrode layer 12 may be co-sintered at approximately 1,450°C for approximately 5 hours to produce a PCEC half-cell.
[0059] During the ultrasonic spray coating process, the ink may be filled into an ultrasonic reservoir to maintain good dispersion of the ink. Furthermore, the ultrasonic nozzle generates highly dispersed droplets, enabling the production of a uniform, ultrathin proton-conducting electrolyte. The anode substrate is also important for a high-quality electrolyte. In this disclosure, a two-layer anode substrate may be used. The electrolyte ink is coated onto the anode functional layer. This anode functional layer does not need to contain a porosizing agent, exhibits low porosity, and produces a highly flat surface. This smooth anode functional layer is one of the main factors for producing a thin, uniform, and dense electrolyte. A porous anode layer can increase the active surface area and ensure rapid mass transport.
[0060] In various embodiments, as shown in Figure 2, LT-PCECs with ultrathin, bamboo-structured (single-grain thickness), chemically homogeneous electrolytes may be fabricated by a scalable and cost-effective ultrasonic spray coating process that can minimize the resistance of proton conduction across grain boundaries. More specifically, as shown in Figure 2, schematic diagrams of PCEC electrolytes fabricated using (a) an ultrasonic spray coater and (b) a conventional airbrush are provided. Ultrasonic spray coating can result in an ultrathin, bamboo-structured (single-grain thickness), chemically homogeneous electrolyte with larger particle sizes and fewer grain boundaries. The conventional airbrush method (compressed air spray) can result in a thin, multi-grain thickness electrolyte with smaller particle sizes and more grain boundaries. As a result, grain boundaries have much lower proton conductivity than the interior of the crystal grains. The arrows in Figure 2 indicate that proton conduction encounters high resistance at grain boundaries, and therefore, electrolytes prepared by ultrasonic spray coating have higher proton conductivity.
[0061] As a result, the use of ultrasonic spray coating reduces the area specific ohm resistance (ASR) caused by the electrolyte. o ) decreased.
[0062] Poor sinterability and evaporation of Ba are two major challenges associated with the fabrication of proton-conducting electrolytes. It is also well known that grain boundaries have lower conductivity than intragranular areas. Therefore, fabricating PCECs with ultrathin, large grains and chemically homogeneous electrolytes may be one of the most essential steps for achieving high performance. In this specification, the inventors coat the negative electrode with an electrolyte using an ultrasonic spray coating system, which is scalable and reproducible. Furthermore, high-quality PCECs with relatively large surface areas have been fabricated using the ultrasonic spray coating system, resulting in a uniform thickness, dense, and defect-free PCEC electrolyte, further demonstrating the feasibility of adopting this process for large-scale PCEC manufacturing. In addition, ultrasonic spray coating improved the microstructure and conductivity of the PCEC electrolyte compared to conventional compressed air spray coaters.
[0063] The conductivity of the electrolyte was measured using EIS, and intragranular conductivity and intergranular conductivity were determined by a comprehensive analysis of the EIS spectrum. The electrolyte powder was subjected to a uniaxial dry press to form pellets with a diameter of 20 mm at a pressure of 150 bar, and then sintered at 1450°C for 5 hours. The resulting pellets were polished with sandpaper to obtain a flat surface with a thickness of approximately 1 mm. Platinum (Pt) paste was used as a current collector for the pellets (effective area 0.5 cm²). 2 The BCZYYb4411 electrolyte pellet was applied to both sides of the pellet by brush coating, and then baked at 350°C for 30 minutes. The ohm resistance of this BCZYYb4411 electrolyte pellet was measured by EIS under a humidified argon atmosphere (3% water vapor) at 500-250°C. Before each measurement, the pellet was held at each temperature for approximately 1 hour to achieve a steady state.
[0064] EIS spectra were collected using the Gamry1010 interface. The obtained impedance spectra were then analyzed using Zview software to separate and analyze bulk resistance and grain boundary resistance. Bulk conductivity and grain boundary conductivity were calculated using the "brick layer model".
[0065] By the ultrasonic spray coating method, the electrolyte layer can have a dense and uniform thickness. Furthermore, these electrolytes include a bamboo structure, and ASR O has been observed to be low. The PCEC produced by this simple coating and co-sintering process is reproducible. In certain embodiments, the electrolyte surface has an average grain size larger than the thickness of the electrolyte. Accordingly, in such embodiments, the PCEC obtained via this process has a small grain boundary area and low ASR O and a quasi-2D electrolyte exhibiting the same.
[0066] As described above, the ultra-thin electrolyte layer 14 may exhibit a bamboo structure in which grain boundaries appear perpendicular to the negative electrode 12. Furthermore, the thin electrolyte layer 14 may be chemically homogeneous, also exhibiting a homogeneous element distribution, suggesting that the chemical composition is consistent throughout the electrolyte. Elemental segregation at grain boundaries can introduce positive potential and reduce proton conductivity. As a result, the PCEC fabricated in accordance with the present disclosure has an ASR that is lower than that of PCECs fabricated by expensive and complex prior art techniques O or can achieve an ASR that is lower than or equivalent to O that.
[0067] In one or more embodiments, the proton-conductive electrolyte layer 14 has an average grain size of at least 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5 or 7 μm. Additionally or alternatively, the proton-conductive electrolyte layer 18 has an average grain size of less than 15, 14, 13, 12, 11, 10, 9, 8, 7, 6, 5, 4 or 3 μm. This smaller grain size may result from the ultrasonic spray coating method. It has also been observed that PCECs fabricated using ultrasonic spray coating rather than conventional air brushing may exhibit reduced ASR O , indicating that electrolytes with larger grain sizes and fewer grain boundaries have higher proton conductivity.
[0068] Once formed, the thickness of the proton-conductive electrolyte 14 may be in the range of about 0.01 μm to about 75 μm, about 1 μm to about 25 μm, about 5 μm to about 15 μm, or about 10 μm.
[0069] In one or more embodiments, the electrochemical cell 10 includes a positive electrode 16. Although it is referred to as the "positive electrode", it will be appreciated that the positive electrode 16 can function as an anode or a cathode depending on the operating mode used. In particular, when the cell 10 operates in a hydrogen production mode, the positive electrode 16 (functioning as an anode) uses electric current to form protons and oxygen from water, and when the cell 10 operates in a power generation mode, the positive electrode 16 (functioning as a cathode) reacts protons and electrons with oxygen to form water.
[0070] In various embodiments, the positive electrode 16 comprises, consists essentially of, or consists of the solid composite material described herein. In one or more embodiments, the positive electrode 16 comprises at least 50, 75, 90, 95, or 99 wt% of the solid composite material.
[0071] An objective of the present disclosure is to reduce the ASR of the PCEC P to less than 0.4Ωcm at 450°C 2 and further improve PCEC performance below 450°C. Accordingly, an in-situ formed composite positive electrode constructed from the solid composite materials described herein has been developed. More specifically, to reduce the ASR P , a positive electrode was developed using double perovskite phase and single perovskite phase nanoparticles.
[0072] In one or more embodiments, the in-situ formed positive electrode powder was synthesized by the wet chemical method described above for producing the solid composite materials described herein. For example, in certain embodiments, stoichiometric amounts of Pr6O 11 , Ba(NO3)2, Sr(NO3)2, Co(NO3)2·6H2O, and Fe(NO3)3·9H2O may be utilized as precursors. Briefly, calculated amounts of Pr6O 11First, a praseodymium nitrate solution may be obtained by dissolving it in a 20 wt% dilute nitric acid solution at 100°C. Then, in such embodiments, stoichiometric amounts of Ba(NO3)2, Sr(NO3)2, Co(NO3)2·6H2O and Fe(NO3)3·9H2O may be added to the praseodymium nitrate solution, and the mixture may be stirred for 30 minutes. Next, citric acid (CA) and ethylenediaminetetraacetic acid (EDTA), which are complexing and chelating agents, may be added to the solution in a molar ratio of CA:EDTA:total cations of 2:2:1, and the mixture may be stirred continuously at room temperature for 1 hour for complete complexation. The pH may be adjusted to about 9 by adding an aqueous solution of NH4OH. The solution may then be heated at 250°C until a gel is formed. The gel may be immediately placed in a drying oven at 175°C for 24 hours. The resulting black powder may then be calcined at 600°C under air for 5 hours, followed by ball milling in ethanol for 1 day, and then dried at 100°C. When sintered at 765°C, the fired powder crystallizes to form a solid composite material powder.
[0073] In one or more embodiments, a specified amount (e.g., 5 grams) of solid composite material powder may be dispersed in a dispersant (e.g., 1 gram of 20% by weight solsperse 28000 (Lubrizol) dissolved in α-terpinol) and a binder (e.g., 0.5 grams of 5% by weight V-006 (Heraeus) dissolved in α-terpinol), then mixed and ground to form a positive electrode slurry.
[0074] The obtained slurry may be applied to the electrolyte layer 14 using a conventional coating method such as ultrasonic spray coating in order to form the positive electrode layer 16.
[0075] In one or more embodiments, at least a portion of the positive electrode slurry may be brushed onto the electrolyte layer 14, and then the PCEC single cell may be directly sealed into an alumina tube without pre-sintering the positive electrode.
[0076] Once formed, the thickness of the positive electrode 16 may be in the range of approximately 10 μm to approximately 70 μm, approximately 20 μm to approximately 60 μm, approximately 20 μm to approximately 50 μm, or approximately 30 μm.
[0077] It has been observed that the catalytic activity of the electrode can be improved by using a cathode formed from the solid composite material described herein.
[0078] In one or more embodiments, the positive electrode formed from a solid composite material has a resistance of at least 0.1, 0.5, 1.0, or 1.2 Ωcm at 400°C. 2 , and / or 9, 8, 7, 6, 5, 4, 3, 2 or 1.5 Ωcm 2 Area-to-electrode polarization resistance less than ("ASR") P The following can be shown: Additionally or alternatively, a positive electrode formed from a solid composite material may have a resistance of at least 0.1, 0.2, 0.3, 0.4, 0.5, 0.6 or 0.7 Ωcm at 450°C. 2 , and / or 4, 3, 2 or 1 Ωcm 2 ASR less than P This may be demonstrated. Additionally or alternatively, a positive electrode formed from a solid composite material may exhibit a resistance of at least 0.05, 0.1, or 0.15 Ωcm at 500°C. 2 , and / or 1, 0.9, 0.8, 0.7 or 0.6 Ωcm 2 ASR less than P This may be demonstrated. Additionally or alternatively, a positive electrode formed from a solid composite material may have a impedance of at least 0.01, 0.05, or 0.1 Ωcm at 550°C. 2 , and / or 1, 0.9, 0.8, 0.7, 0.6, 0.5 or 0.4 Ωcm 2 ASR less than P This may be demonstrated. Additionally or alternatively, a positive electrode formed from a solid composite material may exhibit a resistance of at least 0.01 or 0.05 Ωcm at 600°C. 2 , and / or 1, 0.9, 0.8, 0.7, 0.6, 0.5, 0.4 or 0.3 Ωcm 2 ASR less than P This could demonstrate that.
[0079] Furthermore, in one or more embodiments, the cathode formed from the solid composite material may exhibit an activation energy of at least 10, 25, 50, 75, 80, or 85 kJ / mol and / or less than 150, 130, 110, 105, or 100 kg / mol. This indicates that the cathodes described herein can function as promising cathodes at lower operating temperatures.
[0080] In one or more embodiments, a cathode formed from a solid composite material may exhibit oxygen temperature-triggered desorption (O2-TPD) having (a) one peak at temperatures of at least 200°C, 215°C, or 230°C, and / or below 320°C, 310°C, 300°C, 290°C, 280°C, 270°C, or 260°C, and (b) a second peak at temperatures of at least 200°C, 225°C, 250°C, 275°C, or 290°C, and / or below 380°C, 370°C, 360°C, 350°C, 340°C, 330°C, 320°C, 310°C, or 300°C. These indicate oxygen mobility and oxygen diffusion at the electrode. In this test, two main peaks were observed in the cathode material, likely due to the absorption of oxygen molecules on surfaces exhibiting different binding energies. The corresponding peak temperature of the cathode material of this disclosure has been observed to be lower than that of the prior art, indicating that surface oxygen on the electrode of the present invention is more easily released from the surface, leading to an improvement in oxygen surface oxygen exchange dynamics.
[0081] Both surface oxygen exchange dynamics and bulk oxygen ion diffusion dynamics, as measured by electrochemical conduction relaxation ("ECR") experiments, are essential for high OER and ORR activity. In one or more embodiments, the cathode formed from a solid composite material is heated at 500°C or 550°C for at least 10°C. -7 Or 10 -6 cm 2 s -1 and / or 10 -4 cm 2 s -1 Bulk oxygen ion diffusion coefficient less than ("D") chem The electrode of the present invention exhibits a higher bulk oxygen ion diffusion coefficient (D) than conventional electrodes. chemIt has been observed that the electrodes of the present invention exhibit improved oxygen ion diffusion in bulk.
[0082] Two samples were prepared for the ECR test. First, the sample was pressed axially at 100 bar for 2 minutes using a 2 cm (diameter) die, and then densified by sintering at 1,250°C for 3 hours. A rod was fabricated using a high-precision diamond saw. ECR measurements were performed at 700°C, 650°C, 600°C, 550°C, and 500°C. At each temperature, the oxygen concentration was initially set to 2 vol% (10 sccm O2 + 490 sccm Ar). ECR was measured using the four-probe method, where a current of 40 mA was applied and the voltage was measured. Once the voltage reached equilibrium, the oxygen concentration was immediately changed from 2 vol% to 20 vol%. The voltage response was recorded. Surface exchange coefficient (k chem ) and bulk diffusion coefficient (D chem Relative conductivity change data was calculated using the NETL ECR analysis tool, which measures ).
[0083] Similarly, in one or more embodiments, the positive electrode formed from a solid composite material is heated at 500°C or 550°C for at least 10 -5 Or 10 -4 cm s -1 , and / or 10 -3 cm s -1 Surface oxygen exchange coefficient (k) less than chem The electrode of the present invention may exhibit a higher surface oxygen exchange coefficient (k) compared to conventional electrodes formed solely from two-phase perovskite. chem It was observed that the electrode of the present invention exhibits the following characteristics. For example, at 550°C, the k chem The k of conventional electrodes formed solely from a double perovskite phase chem This can be more than twice as much, meaning that a single perovskite phase is beneficial in accelerating surface oxygen exchange dynamics.
[0084] This also matches the O2-TPD profile. In one or more embodiments, the positive electrode formed from a solid composite material has a D2-TPD of at least 50, 75, or 100 kJ / mol and / or less than 175, 150, or 125 kJ / mol. chem It may exhibit an activation energy related to . Similarly, in various embodiments, the positive electrode formed from a solid composite material may have an activation energy of at least 20, 40 or 60 kJ / mol and / or less than 100, 90, 80 or 70 kJ / mol. chem The activation energies associated with these energies are observed to be lower than those of conventional electrodes formed from the double perovskite phase alone, further highlighting the promising performance at lower operating temperatures. While we do not wish to be bound by theory, a synergistic effect appears to exist between the double perovskite phase and the single perovskite phase in the solid composite materials described herein, resulting in improved electrodecatalytic activity, particularly below 450°C.
[0085] As demonstrated by electrochemical impedance spectroscopy (EIS) of PCEC collected at 450°C under OCV conditions, the cathode of the present invention, formed from a solid composite material, can reduce the ASRp to one-fifth compared to conventional electrodes.
[0086] Analysis of the relaxation time distribution ("DRT") can be provided by a graph plot (defined by graph peaks) divided into three main regions corresponding to oxygen mass transport, oxygen exchange at the cathode, and charge transfer processes, namely the low-frequency region (below 100 Hz), the intermediate-frequency region (100 to 10,000 Hz), and the high-frequency region (above 10,000 Hz). In one or more embodiments, the cathode formed from a solid composite material has an Ω / cm² of at least 0.01, and / or 1.0, 0.9, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, or 0.2 Ω / cm² at 450°C in the low-frequency region. 2It may exhibit a DRT of less than 0.01, and / or 1.0, 0.9, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, or 0.2 Ω / cm² at 450°C in the intermediate frequency region. 2 It may exhibit a DRT of less than 0.01, and / or 1.0, 0.9, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, 0.2, or 0.1 Ω / cm at 450°C in the high-frequency range. 2 It may exhibit a DRT of less than 0. In general, the electrodes of the present invention can exhibit lower DRT peaks at low and medium frequencies compared to conventional electrodes formed solely from a double perovskite phase, indicating that the electrodes of the present invention exhibit improved surface oxygen exchange dynamics, which may be due to the porous structure of the electrodes of the present invention.
[0087] In one or more embodiments, the positive electrode formed from a solid composite material is at least 5, 6, 7, 8, or 9 m 2 / g, and / or 20, 19, 18, 17, 16, 15, 14, 13, 12, 11 or 10m 2 It may have a BET measurement surface area of less than / g. Nitrogen Brunauer, Emmett, Teller (BET) surface area analysis and O2 thermal desorption (O2-TPD) may be performed using a ChemBET Pulsar chemisorption analyzer.
[0088] Spin polarization DFT calculations were performed to study bulk oxygen vacancy formation and oxygen diffusion in double perovskite phases, single perovskite phases, and conventional double perovskite phases. Based on the DFT calculations, it was observed that higher concentrations of Sr and appropriate mixing of Fe help stabilize Ov and lower the oxygen vacancy formation energy.
[0089] The solid composite material of the present invention exhibits excellent ORR performance due to the high oxygen diffusivity of the combined double perovskite phase and single perovskite phase. a , bulkIt was observed that the eV levels of the double perovskite phase (BSC) of the present invention followed a descending order: single perovskite phase (BSC) (2.12 eV) > prior art double perovskite phase (PBSCF-1) (0.88 eV) > double perovskite phase (PBSCF-2) of the present invention (0.51 eV). a , bulk This is 0.37 eV lower than that of the conventional double perovskite phase. The energy difference significantly affects atomic oxygen diffusion and correlates very well with the measured diffusivity.
[0090] Oxygen diffusion within the bulk lattice was modeled using the Climbing Image Nudged Elastic Band (CI-NEB) method and the dimer method. The two vacancy sites with the lowest formation energy (Ov1 and Ov2) were marked. The structure with the most stable oxygen vacancy ("Ov1") is considered the initial state of lattice oxygen diffusion ("IS"), and the structure with the most stable, closest oxygen vacancies is determined to be the final state ("FS"). The diffusion pathway of the double perovskite phase intersects a "critical triangle" formed by one Co atom at the B site and two Pr atoms at the A site, as described by Mastrikov. Diffusion energy barrier (E a,bulk The following formula was used to calculate ):
[0091] E a,bulk =E ts -E initial ,
[0092] Here, E ts and E initial These represent the total energy of the transition state and the initial state, respectively.
[0093] The observed surface exchange rate can also be observed using DFT analysis. Oxygen surface exchange coefficient (k chem ) is the bulk oxygen vacancy formation energy (ΔE Ov It was observed that it changes linearly with respect to ΔE. Ov The lower k chem This indicates that the k is high. Thus, the high k observed in the single perovskite phase (BSC)chem This can also be well explained based on the calculated trend of oxygen vacancy formation energy.
[0094] All DFT calculations presented were performed using the Vienna Ab Initio Simulation Package (VASP). Core electron and electron exchange correlation effects were considered using projector-enhanced wave (PAW) pseudopotentials and the GGA-PBE function. The plane-wave basis set was extended with a 400 eV cutoff energy and Gaussian smearing (σ=0.02 eV). The first Brillouin zone of the reciprocal lattice of the bulk model was sampled using a 4×4×4 k-point mesh generated by the Monkhorst-Pack method. The structure and energy of all transition states were obtained from the climbing-image nudged elastic band (CI-NEB) method and the dimer method.
[0095] Oxygen vacancy sites were tested at all symmetrically distinct locations within the lattice. All structures of the perovskite phase were visualized using VESTA software. Bulk oxygen vacancy formation energy (ΔE Ov ) was defined by the following equation (1).
[0096] ΔE Ov =E Ov +0.5*E O2 -E bulk
[0097] Here, E Ov , E O2 and E bulk These are the energies of the bulk structure, which has oxygen vacancies, gaseous oxygen molecules, and a structure without vacancies, respectively.
[0098] A synergistic effect may be supported by the solid composite materials of the present invention described herein, in which the single perovskite phase (BSC) top layer facilitates surface oxygen exchange by combining the trends of oxygen diffusivity and surface exchange coefficient. Alternatively, a double perovskite phase (PBSCF) may also have a lower E due to the promotion of oxygen vacancy formation. a ,bulk It has the ability to improve bulk diffusion.
[0099] Positive electrodes formed from the solid composite materials described herein have been observed to simultaneously reduce ohmic resistance and corresponding activation energy. For example, in one or more embodiments, a PCEC including a positive electrode formed from the solid composite material described herein exhibits an ohmic resistance of at least 0.01 Ωcm at 400°C. 2 , and 0.5, 0.4 or 0.3 Ωcm 2 ASR less than O This may be demonstrated. Additionally or alternatively, a PCEC comprising a positive electrode formed from the solid composite material described herein exhibits a resistance of at least 0.01 Ωcm at 450°C. 2 , and 0.4, 0.3 or 0.25 Ωcm 2 ASR less than O This may be demonstrated. Additionally or alternatively, a PCEC comprising a cathode formed from the solid composite material described herein may exhibit a resistance of at least 0.01 Ωcm at 500°C. 2 , and 0.4, 0.3, 0.25 or 0.2 Ωcm 2 ASR less than O This could demonstrate that.
[0100] Furthermore, in one or more embodiments, the PCEC including a positive electrode formed from the solid composite material described herein has an ASR of at least 1, 5, 10 or 20 kJ / mol and less than 50, 40, 33, 32 or 31 kJ / mol. O It can indicate the activation energy.
[0101] The expansion coefficient measurement results also showed that the positive electrode formed from the solid composite material of the present invention was superior to the positive electrode of the prior art (23.4 × 10⁻⁶). -6 K -1 A lower coefficient of thermal expansion (CTE, 18.0 × 10⁻¹⁰) -6 K -1 It has the properties of improving cathode-electrolyte compatibility and interfacial bonding. Furthermore, the in-situ formed cathode described herein achieves a much lower CTE than other Co-based cathodes reported in the literature.
[0102] Expansion coefficient measurements were performed using a Netzsch DIL 402 Expedis apparatus to measure the linear thermal expansion profile of the cathode sample. Cylindrical samples were used. Briefly, first, 0.6 g of each sample powder was dry-pressed for 1 minute using a stainless steel carbide die set to a pressure of 50 bar to produce a green cylinder. The cylinder was then sintered in air to obtain the desired sample composition (the cylinder of the present invention was fired at 765°C for 5 minutes, and the cylinder of the prior art was fired at 950°C for 5 hours). The linear thermal expansion profile of the sample was measured using a heating and cooling rate of 10°C / min. The dilatometer was calibrated and corrected for each measurement.
[0103] Peel strength tests were also performed to quantify the bonding strength between the cathode and electrolyte and to measure the coherence of the cathode-electrolyte interface. It was observed that using the cathode of the present invention as described herein resulted in more uniform and stronger peel strength, and the solid composite material resulted in a cathode-electrolyte interface with improved chemical bonding and coherence, which reduced the cathode-electrolyte contact resistance and consequently ASR O It showed that it reduces [something].
[0104] In one or more embodiments, the positive electrode of the present invention, formed from the solid composite material described herein, may exhibit an average peel strength of at least 4, 5, 6, 7, 8, or 9 N and / or less than 20, 15, or 14 N over a period of 2, 3, 4, 5, or 6 minutes.
[0105] The positive electrode of the present invention was observed to exhibit an average peel strength of 6.8 N, which is 42% higher than the average peel strength of the conventional positive electrode (4.8 N). Therefore, the positive electrode of the present invention improves electrochemical performance at lower operating temperatures while simultaneously reducing ohmic resistance.
[0106] The peel strength of the positive electrode was measured according to the ASTM D903 180-degree peel strength test standard. Briefly, the test specimen was placed in the peel strength tester by securing the negative electrode with strong double-sided tape. One end of a rectangular piece of tape was attached to the positive electrode, and the other end was fixed to the peel strength tester. The applied force was recorded as a function of time by pulling the tape back into a "U" shape (180°) at a constant speed.
[0107] The HAADF and EDS images of the positive electrode-electrolyte interface of the present invention show that both BSC and PBSCF were observed, which strengthens the chemical bond between the positive electrode and the electrolyte, and therefore ASR O It is thought that this will reduce [something].
[0108] Formation and performance characteristics of proton-conducting ceramic electrochemical cells In various embodiments, high-performance PCECs capable of operating below 450°C may be fabricated by tape casting, followed by an ultrasonic spray coating process, and then using an in-situ formed solid composite material as the cathode.
[0109] In one or more embodiments, the PCEC of the present invention may be manufactured by both tape casting and spray coating methods.
[0110] As described above, the PCEC of the present invention may include an in-situ formed positive electrode composed of the solid composite material described herein. This positive electrode reduces the coefficient of thermal expansion ("CTE"), improves the positive electrode-electrolyte bond, reduces contact resistance, and reduces ASR O This can be further reduced. Furthermore, this cathode may simultaneously promote surface oxygen exchange and bulk oxygen ion diffusion, especially at low operating temperatures, which can reduce ASR. P This significantly reduces the impedance (compared to 0.76 Ωcm for the positive electrode of conventional technology). 2 ASR P (In contrast) very low ASR at 450℃ P (For example, approximately 0.38 Ωcm) 2 ) makes it possible to achieve this.
[0111] Furthermore, as will be discussed later, the LT-PCEC with the low-resistance electrolyte and cathode described herein can exhibit remarkable performance below 450°C, as demonstrated by its peak power density. For example, at 400°C, it can produce approximately 0.34 Wcm² using H2. -2 This fuel cell PPD can be achieved, doubling the PPD of conventional PCEC technology. Furthermore, for example, in steam electrolysis mode, approximately -1.28 Acm at 1.4V and 450℃. -2 This allows for obtaining a durable current density.
[0112] The PCEC described herein is approximately 0.1 W / cm³ in H2-O2. -2 Effective PCEC fuel cell operation can be achieved at 275°C while achieving a practical PPD. Good stability at 400°C has also been demonstrated with respect to both power generation (degradation rate less than 0.07 mV / h) and hydrogen production (degradation rate less than 0.15 mV / h). Furthermore, the LT-PCEC of this disclosure can produce hydrogen at 400°C with comparable or better rates and electrolytic energy efficiency compared to previously reported PCECs operating above 500°C.
[0113] It has been observed that the open-circuit voltage ("OCV") of the LT-PCEC of the present invention can exceed 1.05V during fuel cell operation, indicating that the PCEC of the present invention, which has an ultrathin, bamboo-structured electrolyte, does not exhibit obvious electron leakage or gas leakage. Furthermore, it has been observed that the LT-PCEC of the present invention can achieve much higher fuel cell performance than PCECs formed using conventional positive electrodes. For example, the LT-PCEC of the present invention (with air, ammonia, hydrogen, and / or oxygen supplied to the positive and / or negative electrodes) can achieve at least 0.01, 0.05, or 0.1 W / cm² at 275°C, 300°C, or 350°C. 2 , and / or 1.8, 1, 0.5, 0.4 or 0.3 W / cm² 2It can exhibit a peak power density of less than 0.5 W / cm². Additionally or alternatively, the LT-PCEC of the present invention can exhibit a peak power density of at least 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, or 0.5 W / cm² at 350°C, 400°C, 450°C, or 500°C (with air, ammonia, hydrogen, and / or oxygen supplied to the positive and / or negative electrodes). 2 , and / or 1.8, 1.6 or 1.4 W / cm² 2 It can exhibit a peak power density of less than 1.0.0, 1.1, or 1.2 W / cm² at 550°C or 600°C (with air, ammonia, hydrogen, and / or oxygen supplied to the positive and / or negative electrodes). Additionally or alternatively, the LT-PCEC of the present invention can exhibit a peak power density of less than 1.0, 1.1, or 1.2 W / cm² at 550°C or 600°C. 2 , and / or 2.0, 1.9 or 1.8 W / cm² 2 It can exhibit a peak power density of less than 1.64 W / cm² at 600°C when air is supplied to the positive electrode. For example, with air supplied to the positive electrode, the LT-PCEC of the present invention exhibits 1.64 W / cm² at 600°C. 2 It is possible to achieve a peak power density ("PPD") of this magnitude, which is greater than the peak power densities of PCEC fuel cells previously reported in the literature.
[0114] In certain embodiments, to compare the LT-PCEC of the present invention with a recently developed PCEC, oxygen is supplied to the positive electrode and approximately 2.0 Wcm³ is produced at 600°C. -2 A PPD of 0.77 Wcm² was achieved, which was higher than that of PCECs with acid-etched electrolytes and 3D cathodes. The LT-PCEC of the present invention can also exhibit remarkable performance below 450°C. For example, in certain embodiments, approximately 0.77 Wcm² was achieved at 450°C. -2 A PPD of 0.77 W / cm² was achieved. Furthermore, in certain embodiments, the positive electrode of the present invention promoted an increase in PPD of approximately 2.7 times compared to the positive electrode of the prior art at 450°C (0.77 W / cm²). 2 Ratio 0.29 W / cm² 2 When the LT-PCEC of the present invention operates at 275°C, approximately 0.1 Wcm of H2-O2 is produced. -2 It was also demonstrated that it can function as a practical fuel cell exhibiting PPD (Power Processing Dispersion).
[0115] LT-PCECs operating below 450°C can also offer good fuel flexibility. In one or more embodiments, when ammonia is supplied to the anode without the use of an additional ammonia decomposition catalyst, the LT-PCEC of the present invention produces approximately 0.65 W / cm² at 500°C. 2 At 450℃, the power consumption is approximately 0.28 W / cm². 2 , and at a low temperature of 400℃, approximately 0.16 W / cm² 2 The PPD was achieved.
[0116] Furthermore, as described above in such embodiments, direct ammonia PCEC also exhibits excellent performance at 500-600°C, with a wattage of approximately 1.38 W / cm² at 600°C. 2 We were able to achieve a PPD of 1, which significantly exceeds the results reported in the literature. After performance evaluation under ammonia, there was no evidence of grain boundary fracture, demonstrating that the ultrathin electrolyte fabricated by the LT-PCEC of the present invention is robust under ammonia. The PCEC performance under ammonia was equivalent to that under H2, indicating that the negative electrode is active against ammonia decomposition and suggesting that ammonia can function as an H2 carrier for power generation in PCEC.
[0117] To determine the performance of a PCEC fuel cell using ammonia as fuel, the ammonia flow rate may be set to 40 sccm at 600°C, 35 sccm at 550°C, 30 sccm at 500°C, 25 sccm at 450°C, 20 sccm at 400°C, and 10 sccm at 400°C, and may be varied with the operating temperature to maximize fuel utilization.
[0118] The LT-PCEC of the present invention has been observed to be able to directly utilize methane for power generation. To demonstrate this, an internal steam methane reforming (SMR) catalyst, Sm 0.2 Ce 0.7 Ni 0.1 Ru 0.05 O 2-δBy coating the PCEC anode with , and using methane as fuel at a low operating temperature, even higher performance was achieved. When its catalytic activity was first evaluated in a packed-bed reactor, it was shown that the synergistic effect of Ni and Ru enhances SMR activity. For example, Sm 0.2 Ce 0.7 Ni 0.1 Ru 0.05 O2 achieved the highest CH4 conversion rate at 500°C, which is Sm 0.2 Ce 0.7 Ni 0.15 O 2-δ It is about 35% higher than Sm 0.2 Ce 0.7 Ru 0.15 O 2-δ It was about 26% higher than that. At 450℃, Sm 0.2 Ce 0.7 Ni 0.1 Ru 0.05 The CH4 conversion rate in O2 reached approximately 27%, suggesting that a PCEC equipped with this catalyst can yield a viable power density. To test the PCEC fuel cell performance with methane, SDC-Ni-Ru ink was brushed onto the anode as a catalyst reforming layer. A mixture of methane and water vapor was supplied to the anode at a 1:1 methane-to-water vapor ratio. Here, the CH4 flow rate, set to 16 sccm at 500°C, 12 sccm at 450°C, and 8 sccm at 400°C, was also varied with operating temperature.
[0119] CH4 conversion rate (X CH4 ) may be calculated as follows:
[0120]
number
[0121] In the formula, F in and F out These represent the flow rates of the inlet gas or outlet gas, respectively.
[0122] In a specific embodiment, 0.55 W / cm² at 500°C. 2PPD was observed in methane, while in contrast, for example, in prior art solid oxide fuel cells, it was 0.37 W / cm³ at 500°C. 2 This was observed, approaching the PPD performance of PCEC in pure H2.
[0123] In such embodiments, the PCEC fuel cell performance with methane demonstrates that a viable PPD was still achieved even at 400°C. Thus, in such embodiments, the LT-PCEC fuel cell performance using both ammonia and methane demonstrates the fuel flexibility of PCEC operating below 450°C.
[0124] Furthermore, the hydrogen production of the LT-PCEC of the present invention may be evaluated in an electrolysis mode below 450°C. To evaluate the PCEC electrolysis performance of hydrogen production, a mixture of water vapor and nitrogen was supplied to the positive electrode at a water vapor concentration of 40%. The water vapor concentration was controlled by bubbling nitrogen (100 sccm) through a customized temperature-controlled bubbler. Pure hydrogen gas (15 sccm) was supplied to the negative electrode as a sweep gas.
[0125] To evaluate the Faraday efficiency (FE), the negative electrode outlet gas was mixed with a nitrogen gas stream, and then injected into an online gas chromatograph (INFICON3000 Micro GC) to quantify the hydrogen production rate. This method allowed for the evaluation of PCEC electrolysis performance under realistic conditions and the accurate determination of FE. FE (%) was calculated using the following formula.
[0126]
number
[0127] Here, FE(%) is the Faraday efficiency at different current densities.
number
[0128] To simulate the electrolysis performance of PCEC under industrially relevant conditions, a stream of H2 may be supplied to the anode as a sweep gas. Conventionally, Ar or a dilute H2 stream may be used as a sweep gas to test laboratory-scale PCEC, which allows for accurate measurement of the outlet gas concentration and quantification of FE using GC. However, in PCEC laminates or PCEC systems, dry, pure H2 is produced at the anode. A sweep gas is not required for hydrogen production at the laminate or system level. Therefore, in this disclosure, the electrolysis performance of a laboratory-scale PCEC is evaluated using pure H2 as a sweep gas, which can better represent the performance of a commercial-scale PCEC. The H2 stream is then diluted by mixing the outlet gas with nitrogen, enabling quantification of the hydrogen production rate using GC.
[0129] In one or more embodiments, the LT-PCEC of the electrolysis mode of the present invention is at 1.4 V and 450 °C, with a voltage of at least -1.6, -1.5, or -1.4 Acm². -2 , and / or -0.5, -0.8, -1.0 or -1.1 Acm -2 It exhibits a current density of less than . Additionally or alternatively, the LT-PCEC of the electrolysis mode of the present invention exhibits at least -1.0, -0.9, or -0.8 Acm at 1.4 V and 400 °C. -2 , and / or -0.5, -0.6 or -0.7 Acm -2 It may exhibit a current density of less than . Additionally or alternatively, the LT-PCEC of the electrolysis mode of the present invention exhibits at least -0.01, -0.02, or -0.03 Acm at 1.4 V and 350 °C. -2 , and / or -0.5, -0.6 or -0.7 Acm -2 It may exhibit a current density of less than [amount missing].
[0130] For example, the PCEC of the present invention produces approximately -1.28 Acm at 1.4 V and 450°C. -2While it is possible to achieve a current density of 1.04 Acm², conventional PCEC technology achieves, for example, 1.04 Acm² at 450°C. -2 It has been observed that a current density of 0.4, 0.6, or 0.8 Acm can be achieved. Furthermore, in one or more embodiments, the LT-PCEC electrolysis mode of the present invention achieves a current density of 0.4, 0.6, or 0.8 Acm at 400°C. -2 And it can exhibit a Faraday efficiency ("FE") of at least 70, 75, 80, 85, 90, or 95%.
[0131] Furthermore, 400℃ and 0.6Acm -2 At this current density, the cell-level electrical-to-chemical energy conversion efficiency of the LT-PCEC of the present invention can reach at least 77%, demonstrating the feasibility of producing hydrogen at temperatures below 450°C using the PCEC of the present invention.
[0132] It is important to recognize that a relatively low FE(%) in PCEC can be one of the main challenges. Low FE(%) is typically due to p-type electron leakage across the electrolyte. p-type electron leakage is a reaction of oxidation (
number
[0133] PCEC stability tests were also evaluated for power generation and hydrogen production at temperatures below 450°C. In certain embodiments, 300 mAcm was used. -2 At a current density of 400°C, the LT-PCEC of the present invention can operate continuously for at least 100 hours in fuel cell mode, achieving a degradation rate of less than 0.07 mV / h. After this time, there are no observable changes in the microstructure and no cracks in the electrolyte. The cathode-electrolyte interface may no longer show delamination, which suggests that the interfacial bonding is good and thermal expansion is adaptable.
[0134] The LT-PCEC of the present invention also showed excellent long-term stability in the electrolysis mode at 400°C. In one or more embodiments, the PCEC of the present invention was -0.6Acm -2 When operated for at least 250 hours at the current density, it is possible to achieve low degradation of applied voltage (less than 0.15 mV / h) and FE. While we do not wish to be bound by theory, the durability of the LT-PCEC of the present invention enables the first-ever H2 production using PCEC at 400°C, which dramatically reduces the required operating temperature and is considered to surpass the performance of previous PCECs. The stable terminal voltage and FE of the PCEC of the present invention do not suggest significant degradation. In certain embodiments, subsequent microstructural analysis of the PCEC of the present invention shows no evidence of degradation after the long-term durability test parameters described above. Specifically, no cracks are observed in the electrolyte, which is essential for high Faraday efficiency. Furthermore, in certain embodiments, there is no evidence of cathode decomposition and / or electrolyte-cathode delamination after the long-term durability test parameters described above, thereby highlighting the robustness of the PCEC of the present invention for H2 production.
[0135] By fabricating ultrathin, single-grain thickness, chemically homogeneous, and low-resistance electrolytes and developing in-situ formed composite cathodes, high-performance PCECs capable of both power generation and hydrogen production at temperatures below 450°C were created. PCEC electrolytes fabricated by simple and scalable processes may exhibit resistance equivalent to or lower than PCECs fabricated by expensive and complex processes. Furthermore, in-situ formed cathodes formed from the solid composite materials described herein may exhibit significantly improved electrode catalytic activity and reduced cathode-electrolyte contact resistance. At 450°C, the PCECs of the present invention demonstrated excellent performance in both fuel cell mode and steam electrolysis mode. The PCECs of the present invention may exhibit long-term endurance fuel cell performance and remarkable durability in the electrolysis mode at 400°C. These reproducible results further highlight the potential of using the PCECs of the present invention for large-scale, efficient power generation and hydrogen production.
[0136] Electrical assemblies and other applications Depending on the operating mode used, the proton-conducting ceramic electrochemical cell 10 can produce hydrogen or generate electricity.
[0137] To produce hydrogen, the proton-conducting ceramic electrochemical cell 10 operates in a hydrogen production configuration. During this configuration, water, preferably in the form of water vapor, reacts at the negative electrode 12 to produce oxygen, electrons, and protons via an oxygen evolution reaction that occurs at a temperature of about 300°C to about 700°C. The generated protons may then pass through the proton-conducting electrolyte 14 to reach the positive electrode 16. Simultaneously, an electric current may be supplied to the positive electrode 16 from an external source such as a solar panel. The positive electrode 16 may reduce at least some of the protons to form hydrogen via a hydrogen evolution reaction that occurs at a temperature of about 300°C to about 700°C.
[0138] To generate electricity, the proton-conducting ceramic electrochemical cell 10 operates in an electro-production configuration. In this configuration, hydrogen is supplied to the cell 10, and the hydrogen is oxidized at the negative electrode 12 via a hydrogen oxidation reaction that occurs at a temperature of about 300°C to about 700°C to produce electrons and protons. In most embodiments, the supplied hydrogen is hydrogen previously formed while the cell 10 is operating in a hydrogen production configuration. The generated protons pass through the proton-conducting electrolyte 14 to the positive electrode 16, where they react with oxygen to produce water via an oxygen reduction reaction that occurs at a temperature of about 300°C to about 700°C. Simultaneously, the generated electrons induce an electric current, which reaches the positive electrode 16 through an electrical load. The electrical load is connected to the negative electrode 12 and the positive electrode 16. In various embodiments, the electrons induce an open-circuit voltage of the cell of about 0.5V to about 1.50V, about 0.75V to about 1.25V, about 1.0V to about 1.1V, or about 1.05V.
[0139] The disclosure also relates to a method for producing hydrogen. In one or more embodiments, the method includes providing a proton-conducting ceramic electrochemical cell, reacting water at the negative electrode to produce oxygen and protons, allowing the protons to pass through an electrolyte to the positive electrode, and supplying an electric current to the negative electrode to reduce at least a portion of the protons to form hydrogen.
[0140] During operation, the proton-conducting ceramic electrochemical cell 10 operates at temperatures of approximately 200°C to 1000°C, approximately 350°C to 850°C, approximately 400°C to 700°C, below 450°C, or below 400°C.
[0141] The disclosure also relates to a method for generating electricity. In one or more embodiments, the method includes (a) providing a proton-conducting ceramic electrochemical cell; (b) supplying hydrogen to the electrochemical cell and oxidizing the hydrogen at the negative electrode 12 to form protons and electrons; (c) allowing the protons to pass through the electrolyte layer 14 to reach the positive electrode 16; (d) inducing an electric current in the electrons generated at the negative electrode 12 and passing the current through an electrical load connected to the negative electrode 12 and the positive electrode 16; and (e) reacting the protons with oxygen at the positive electrode 16 to produce water.
[0142] definition Please understand that the following is not intended to be an exclusive enumeration of defined terms. Other definitions may be provided in the above explanation, for example, when used in context.
[0143] As used herein, the terms “a,” “an,” and “the” mean one or more.
[0144] As used herein, the term “about” refers to a range of ±10% of the stated value. For example, “about 10” encompasses the range from 9 to 11.
[0145] As used herein, the term "and / or" means, when used in the enumeration of two or more items, that any one of the enumerated items may be used alone, or any combination of two or more of the enumerated items may be used. For example, if a composition is described as containing components A, B and / or C, the composition may contain A alone, B alone, C alone, a combination of A and B, a combination of A and C, a combination of B and C, or a combination of A, B and C.
[0146] As used herein, the terms “comprising,” “comprises,” and “comprise” are unrestricted transitional terms used to move from the subject listed before the term to one or more elements listed after the term, and the one or more elements listed after the transitional term are not necessarily the only elements that constitute the subject.
[0147] As used herein, the terms “having,” “has,” and “have” have the same unrestricted meaning as “comprising,” “comprises,” and “comprise” as defined above.
[0148] As used herein, the terms “including,” “include,” and “included” have the same unrestricted meaning as “comprising,” “comprises,” and “comprise” as defined above.
[0149] Numerical range This specification uses numerical ranges to quantify certain parameters relating to the invention. Where a numerical range is given, it should be understood that such a range should be interpreted as providing literal support for limitation of claims that enumerate only the lower limits of the range and limitation of claims that enumerate only the upper limits of the range. For example, the disclosed numerical range of 10 to 100 literally supports claims that state "greater than 10" (without an upper limit) and claims that state "less than 100" (without a lower limit).
[0150] Claims not limited to the disclosed embodiments The preferred embodiments of the present invention described above should be used for illustrative purposes only and not in a restrictive sense to interpret the scope of the invention. Modifications to the exemplary embodiments described above can be readily made by those skilled in the art without departing from the spirit of the invention.
[0151] The inventors hereby declare their intention to rely on the doctrine of equivalents to determine and evaluate the reasonably fair scope of the invention with respect to devices that do not substantially deviate from the literal scope of the invention as described in the following claims, but fall outside that literal scope.
Claims
1. A positive electrode for a proton-conducting ceramic electrochemical cell, comprising a solid composite material, wherein the solid composite material comprises a double perovskite phase and a single perovskite phase.
2. The positive electrode according to claim 1, wherein the double perovskite phase comprises PrBaSrCoFeO ("PBSCF") and the single perovskite phase comprises BaSrCoO ("BSC").
3. The positive electrode according to claim 2, wherein the molar ratio of barium to strontium in the double perovskite phase is 0.1:1 to 1:
1.
4. The positive electrode according to claim 3, wherein the molar ratio of praseodymium to barium in the double perovskite phase is 1.5:1 to 15:
1.
5. The positive electrode according to claim 4, wherein the molar ratio of praseodymium to strontium in the double perovskite phase is 1.5:1 to 3.5:
1.
6. The positive electrode according to claim 5, wherein the molar ratio of praseodymium to cobalt in the double perovskite phase is 0.5:1 to 1.5:
1.
7. The positive electrode according to claim 6, wherein the molar ratio of praseodymium to iron in the double perovskite phase is 1.5:1 to 2.5:
1.
8. The positive electrode according to claim 7, wherein the molar ratio of barium to strontium in the single perovskite phase is 1.5:1 to 2.0:
1.
9. The positive electrode according to claim 8, wherein the molar ratio of barium to cobalt in the single perovskite phase is 0.5:1 to 0.75:
1.
10. The positive electrode according to claim 9, wherein the molar ratio of strontium to cobalt in the single perovskite phase is 0.25:1 to 0.5:
1.
11. said double perovskite phase has the formula Pr a Ba b Sr c Co d Fe e O 6-δ1 , and said single perovskite phase has the formula Ba x Sr y Co z O 3-δ2 , where in the formula, a is between 1 and 1.
75. b is between 0.05 and 0.
5. c is between 0.3 and 0.
7. d is between 1.25 and 1.
75. e is between 0.4 and 0.
9. δ1 is greater than 0 but less than 1. x is between 0.4 and 0.
75. y is between 0.25 and 0.
5. z is 0.75 to 1.25, and / or The positive electrode according to claim 2, wherein δ² is greater than 0 but less than 0.
5.
12. The double perovskite phase has a tetragonal (P4 / mmm) crystal structure, and / or the single perovskite phase has a hexagonal P6 crystal structure. 3 The positive electrode according to claim 2, having an mmc crystal structure.
13. The positive electrode according to claim 2, wherein the solid composite material comprises at least 50% by weight of the double perovskite phase based on the total weight of the solid composite material.
14. The positive electrode according to claim 2, wherein the solid composite material comprises at least 10% by weight and less than 50% by weight of the single perovskite phase, based on the total weight of the solid composite material.
15. The positive electrode according to claim 2, wherein the solid composite material has an average particle diameter of at least 1 nm and / or less than 100 nm, as confirmed by TEM.
16. 0.1–4 Ωcm at 400°C 2 ASR P The positive electrode according to claim 2, which shows the above.
17. 0.1–4 Ωcm at 450°C 2 ASR P The positive electrode according to claim 2, which shows the above.
18. The positive electrode according to claim 2, exhibiting an activation energy of 10 to 150 kJ / mol.
19. 5-20m 2 The positive electrode according to claim 2, having a BET measurement surface area of 1 / g.
20. 0.01–0.5 Ωcm at 400°C 2 ASR O The positive electrode according to claim 2, which shows the above.
21. A negative electrode containing a first electrode material, A positive electrode containing a second electrode material, A proton-conducting electrolyte disposed between the negative electrode and the positive electrode, A proton-conducting ceramic electrochemical cell comprising a second electrode material comprising a solid composite material comprising a double perovskite phase and a single perovskite phase.
22. The electrochemical cell according to claim 21, wherein the double perovskite phase comprises PrBaSrCoFeO(PBSCF) and the single perovskite phase comprises BaSrCoO(BSC).
23. The electrochemical cell according to claim 22, wherein the molar ratio of barium to strontium in the double perovskite phase is 0.1:1 to 1:
1.
24. The electrochemical cell according to claim 23, wherein the molar ratio of praseodymium to barium in the double perovskite phase is 1.5:1 to 15:
1.
25. The electrochemical cell according to claim 24, wherein the molar ratio of praseodymium to strontium in the double perovskite phase is 1.5:1 to 3.5:
1.
26. The electrochemical cell according to claim 25, wherein the molar ratio of praseodymium to cobalt in the double perovskite phase is 0.5:1 to 1.5:
1.
27. The electrochemical cell according to claim 26, wherein the molar ratio of praseodymium to iron in the double perovskite phase is 1.5:1 to 2.5:
1.
28. The electrochemical cell according to claim 27, wherein the molar ratio of barium to strontium in the single perovskite phase is 1.5:1 to 2.0:
1.
29. The electrochemical cell according to claim 28, wherein the molar ratio of barium to cobalt in the single perovskite phase is 0.5:1 to 0.75:
1.
30. The electrochemical cell according to claim 29, wherein the molar ratio of strontium to cobalt in the single perovskite phase is 0.25:1 to 0.5:
1.
31. The double perovskite phase is given by formula Pr a Ba b Sr c Co d Fe e O 6-δ1 The single perovskite phase has the formula Ba x Sr y Co z O 3-δ2 It has, in the formula, a is between 1 and 1.
75. b is between 0.05 and 0.
5. c is between 0.3 and 0.
7. d is between 1.25 and 1.
75. e is between 0.4 and 0.
9. δ1 is greater than 0 but less than 1. x is between 0.4 and 0.
75. y is between 0.25 and 0.
5. z is 0.75 to 1.25, and / or The electrochemical cell according to any one of claims 21, wherein δ² is greater than 0 but less than 0.
5.
32. The double perovskite phase has a tetragonal (P4 / mmm) crystal structure, and / or the single perovskite phase has a hexagonal P6 crystal structure. 3 An electrochemical cell according to claim 31, having an mmc crystal structure.
33. The electrochemical cell according to claim 31, wherein the solid composite material comprises at least 50% by weight of the double perovskite phase, based on the total weight of the solid composite material.
34. The electrochemical cell according to claim 31, wherein the solid composite material comprises at least 10% by weight and less than 50% by weight of the single perovskite phase, based on the total weight of the solid composite material.
35. The positive electrode exhibits an impedance of 0.1 to 4 Ωcm at 400°C. 2 ASR P The electrochemical cell according to claim 31, which shows the following.
36. The positive electrode exhibits an impedance of 0.1 to 4 Ωcm at 450°C. 2 ASR P The electrochemical cell according to claim 31, which shows the following.
37. The electrochemical cell according to claim 31, wherein the positive electrode exhibits an activation energy of 10 to 150 kJ / mol.
38. The positive electrode is 5 to 20 m 2 The electrochemical cell according to claim 31, having a BET measurement surface area of 1 / g.
39. The positive electrode has an impedance of 0.01 to 0.5 Ωcm at 400°C. 2 ASR O The electrochemical cell according to claim 31, which shows the following.
40. The electrochemical cell according to claim 31, wherein the positive electrode exhibits an average peel strength of 4 to 20 N as measured according to ASTM D903.
41. 0.01–1 W / cm² at 350°C 2 The electrochemical cell according to claim 31, which shows the peak power density.
42. 0.1–1.4 W / cm² at 400°C 2 The electrochemical cell according to claim 31, which shows the peak power density.
43. An electrical assembly comprising the electrochemical cell according to claim 21, operably connected to an electrical source and / or an electrical load.
44. The electrical assembly according to claim 43, operably connected to a steam source.
45. A method for producing hydrogen, To provide the electrochemical cell described in claim 21, The process involves reacting water at the negative electrode to produce oxygen and protons, The protons are to pass through the proton-conducting electrolyte and reach the positive electrode, The process involves supplying current to the negative electrode and reducing at least a portion of the protons to form hydrogen. Methods that include...
46. A method for generating electricity, To provide the electrochemical cell described in claim 21, The process involves supplying hydrogen to the electrochemical cell and oxidizing the hydrogen at the negative electrode to form protons and electrons, The protons are to pass through the proton-conducting electrolyte and reach the positive electrode, Inducing an electric current in the electrons generated at the negative electrode, and passing the current through an electrical load connected to the negative electrode and the positive electrode, A method comprising reacting the proton with oxygen at the positive electrode to produce water.
47. A method for forming an electrochemical cell according to claim 21, (a) To provide the negative electrode, (b) Forming the proton-conducting electrolyte on the surface of the negative electrode, (c) Forming the positive electrode on the surface of the proton-conducting electrolyte Methods that include...